Catalytic behaviour of a novel Fe(iii) Schiff base complex in the mild oxidation of cyclohexane. Issue 3 (9th January 2015) - Nesterov, Dmytro S.; Nesterova, Oksana V.; Guedes da Silva, M. Fátima C.; Pombeiro, Armando J. L.
Abstract : An iron coordination compound, possessing an unsaturated coordination environment, has been prepared by reaction of FeCl3 with a polydentate Schiff base revealing a complex catalytic behaviour in the mild oxidation of cyclohexane by hydrogen peroxide. Abstract : The complex [Fe III (HL)Cl2 (DMF)]Cl·DMF (1 ) was synthesized by reaction of Fe(iii ) chloride with a dimethylformamide solution of the Schiff base aminoalcohol HL (2-[( E )-{[2-(piperazin-1-yl)ethyl]imino}methyl]phenol) and characterized by single crystal X-ray diffraction analysis, thermogravimetry and spectroscopic methods. The catalytic investigations disclosed a marked activity of1 towards oxidation of cyclohexane with hydrogen peroxide, under mild conditions, with yields based on cyclohexane up to 37% and TONs (turnover numbers) up to ca. 900. Kinetic experiments and selectivity parameters led to the conclusion that hydroxyl radicals are active (attacking C–H bonds) species in the studied catalytic reaction. Kinetic and UV/Vis spectrometry data revealed a complex nature of the processes occurring in the catalytic system, including the transformation of1 into catalytically active species.